GIS-based MCDA approach for FELDA land model development / Suzanah Abdullah ... [et al.] - Abdullah, Suzanah; Mokhtar, Salbiah; Abdul Rashid, Mohd Fadzil; Kamaruddin, Siti Mazwin; Kamar, Muhamad Asri Abdullah; Ali, Mohamad Azal Fikry (2022)
Long-term development has been a top priority for planners in developed countries, as it is a process that requires resources that are compatible with the surrounding environment such as those in the physical, social, institutional, and economic aspects. FELDA plays a proactive role especially to plan, generate and implement land development strategy through plantation projects and poverty eradication programs in rural areas. The transformation of FELDA lands is a crucial and significant issue that must be addressed for the success of sustainability and resilient settlement programs. Hence, there is a need to find alternatives, planning, and solutions to enforce the potential of FELDA's lands towards the highest and best use and enhance the life quality of its settlers. This paper attempts to determine suitable land areas and produce alternative scenarios of feasible developments using the Geographical Information System (GIS)-based Multi Criteria Decisions-Making Analysis (MCDA) approach. In this study, a framework for FELDA land development was applied using an integrated approach of GIS and MCDA techniques as well as UAV technology for data collecting. GIS-based MCDA approach was used to conduct geospatial analyses for evaluating land potential levels and estimate High Best Use (HBU) returns based on what if scenarios. UAV technology was applied to acquire spatial data of FELDA Bukit Rokan areas with a very high-resolution image. The spatial data from UAV imagery was extracted according to a predefined classification. The data were divided into two groups, namely crop areas (plantation areas) and settlements, to get the required outcomes of the land model development. The analysis of GIS-based MCDA has produced the potential area for crops and land development of FELDA. The anticipated results form a composite map of physical growth in the future.